1975
DOI: 10.1002/jsfa.2740260906
|View full text |Cite
|
Sign up to set email alerts
|

Palm kernel meal as the major protein concentrate in the diets of pigs in the tropics

Abstract: Three trials were carried out to determine the suitability of locally produced palm kernel meal ( P K M ) as the major protein concentrate in the diets of weaners, growers and fattening pigs in the tropics. Large White and Large White x Landrace cross barrows and gilts were used. These were individually fed at semirestricted levels the various diets formulated to contain approximately 15, 12 and 16.5 % crude protein for trials 1, 2 and 3 respectively, the PKM or other protein sources contributing at least 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 1 publication
4
19
0
Order By: Relevance
“…This is definitely due to greater concentration of the nutrient because of the lower amount of fat left after the solvent extraction process. The crude fibre values observed were higher than that earlier reported by Babatunde et al (1975). The crude fibre value reported by Olomu (1995) was within the range of values observed in this study.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This is definitely due to greater concentration of the nutrient because of the lower amount of fat left after the solvent extraction process. The crude fibre values observed were higher than that earlier reported by Babatunde et al (1975). The crude fibre value reported by Olomu (1995) was within the range of values observed in this study.…”
Section: Resultssupporting
confidence: 80%
“…For instance, PKM has been found to contain between 16.0 and 21.3% crude protein with low content of lysine, methionine, histidine and threonine (Nwokolo et al, 1977;Olomu, 1995). The crude fibre content ranges from 6.7% (Babatunde et al, 1975) to 17.5% (Olomu, 1995). It has an estimated ash content of 4.30% (Yeong, 1980;NIFOR, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the high fibre level of DP and its gritty nature, which reduce digestibility and possibly the availability of nutrients especially amino acids (Yeong 1983;Onwudike 1986). According to Babatunde et al (1975), the structure of DP is fibrous, and therefore may reduce digestive enzyme action on DP protein and availability of the protein. In agreement with present study, Jumah et al (1973) found that adding DP to broiler diets observed a reduction in body weight gain compared with the control diet (0% DP).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to presence of the high fibre in DP and its gritty nature, which reduce digestibility and possibly the availability of nutrients especially amino acids (Yeong 1983;Onwudike 1986). The fibre in DP, according to Babatunde et al (1975), has lingocellulosic structure; therefore, reducing digestive enzyme action on DP protein and availability of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…This calcium and phosphorus content is in excess of the requirement of .8% cal cium and .6% phosphorus recommended by NRC (1973) for 5 to 10 kg pigs. Babatunde et al (1975) reported that, with about 3.84% calcium and 1.93% phosphorus in the diets of pigs, appetite could be reduced, and feed con sumption significantly depressed. The high calcium and phosphorus level of the basal diet in the present experiment, probably combined with amino acid imbalance, caused poor feed intake at higher levels of feeding and the poor efficiency of utilization of ME for energy gain.…”
Section: Experiments 7610mentioning
confidence: 99%